Partitioning niche and neutral drivers of metacommunity patterns in fish from Brazilian Cerrado streams - Vieira, Thiago Bernardi; Casatti, Lilian [UNESP]; Romero, Renato Mei; Tejerina-Garro, Francisco Leonardo; Uchôa de Aquino, Pedro De Podestà; Pompeu, Paulo Santos; Correia, Letícia Lima; Dias, Samantha Valente; De Marco, Paulo (Elsevier, 2025)
Metacommunity models aim to explain biodiversity patterns by considering different mechanisms. The Species Sorting concept suggests that local environmental conditions and species-specific traits drive community composition. Neutral Theory highlights the stochastic nature of dispersal and extinction, assuming ecological equivalence among species. The Mass Effect concept integrates these perspectives, emphasizing the interaction between environmental gradients and dispersal. In this study, we partitioned fish communities from Brazilian Cerrado streams between niche and neutral processes, identifying the primary drivers of metacommunity structure. We found that species sorting mechanisms played a dominant role, while neutral processes were best represented by linear, Euclidian, distances, particularly those accounting for physical barriers. These findings underscore the importance of considering local habitat variation and natural barriers in conservation strategies. Although artificial barriers were not explicitly included in our distance matrices, their potential impacts on connectivity warrant further investigation.
Keywords: Connectivity; Environmental gradient; Ichthyofauna; Mass effect; Specie sorting; Stream network